The Effect of Situational Leadership Style and Work Motivation on Employee Performance Services of Social, Labor and Transmigration Bombana District - Achmad, Asriani (International Journal of Management and Education in Human Development, 2021)
This study aims to test and analyze empirically the influence of leadership style and work motivation on the performance of the employees of the Research and Development Agency of Southeast Sulawesi Province. This research is an explanatory aims to explain the position of the variables to be studied and the relationship and influence between one variable with another variable. The population in this study were all employees of the Office of the Research and Development Agency of Southeast Sulawesi Province totaling 102 people. Due to the limited number of populations, the researcher determines the number of population units as well as being the research respondents. Data analysis used multiple linear regression analysis. The results showed that: (1) there was a significant influence of leadership style on the performance of Balitbang Prov. Southeast Sulawesi. This means that leadership style contributes significantly to employee performance; (2) there is a significant effect of work motivation on the performance of Balitbang Prov employees. Southeast Sulawesi. This means that work motivation makes a significant contribution to employee performance; and (3) together the two independent variables, namely leadership style and work motivation, have a significant influence on employee performance. Every improvement in leadership style and work motivation will be followed by an increase in employee performance.